Perancangan Film Dokumenter Ekspositori Wayang Orang Sriwedari sebagai Media Pelestarian Budaya bagi Generasi Z - Srilendra Agung Ikramawardhana; Didit Prasetyo; Kartika Kusuma Wardani; Nugrahardi Ramadhani (Institut Seni Indonesia Yogyakarta, 2026)
Designing the Sriwedari Wayang Orang Expository Documentary Film as a Medium for Cultural Preservation for Generation Z. Wayang Orang Sriwedari Surakarta is a traditional performing art that continues to survive amid changes in media consumption and audience preferences. In this context, cultural preservation can no longer be understood solely as maintaining a performance tradition, but also as developing forms of communication that remain meaningful to younger audiences. This study aims to design an expository documentary film about Wayang Orang Sriwedari as a medium of cultural preservation for Generation Z. The design employed four stages: research, pre-production, production, and post-production. Data were collected through field observation, documentation, in-depth interviews, existing studies, and target audience research. The findings indicate that the relevance of Wayang Orang Sriwedari for young audiences is shaped by story adaptation, the use of humor, sensitivity to contemporary issues, and the use of social media. These findings were translated into a documentary with an expository approach and thematic structure to present information in a clear, concise, and communicative manner. The resulting film demonstrates that documentary can function not only as visual documentation, but also as a medium of representation and a cultural communication strategy that is more closely aligned with Generation Z.